2018
DOI: 10.1002/adma.201804574
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the Ocean: Whale Baleen Fracture Resistance

Abstract: Whale baleen is a keratin‐based biological material; it provides life‐long (40–100 years) filter‐feeding for baleen whales in place of teeth. This study reveals new aspects of the contribution of the baleen's hierarchical structure to its fracture toughness and connects it to the unique performance requirements, which require anisotropy of fracture resistance. Baleen plates are subjected to competing external effects of hydration and varying loading rates and demonstrate a high fracture toughness in transverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…It was concluded that in both ambient dry and hydrated conditions, the fracture toughness increases significantly as the crack propagates (Figure e). This can be explained by the extrinsic toughening mechanism shown in Figure f, where the initial cracks which are perpendicular to the tubules are deflected by 90°, and start propagating along the tubules . Crack deflection by the tubular structures is caused by the weak interfaces between the cell lamellae, which is similar to that observed in bone osteons.…”
Section: Microscalementioning
confidence: 64%
See 2 more Smart Citations
“…It was concluded that in both ambient dry and hydrated conditions, the fracture toughness increases significantly as the crack propagates (Figure e). This can be explained by the extrinsic toughening mechanism shown in Figure f, where the initial cracks which are perpendicular to the tubules are deflected by 90°, and start propagating along the tubules . Crack deflection by the tubular structures is caused by the weak interfaces between the cell lamellae, which is similar to that observed in bone osteons.…”
Section: Microscalementioning
confidence: 64%
“…Baleen is a keratinized tissue with a relative low degree of mineralization (around ≈1–4 wt%). It was found that these microstructured tubules inside the baleen contributed to the fracture toughness of the whole structure in the direction perpendicular to the tubules . Figure d shows a schematic of the tubular structure, in which keratinized cells are indicated in both tubule and intertubular areas.…”
Section: Microscalementioning
confidence: 99%
See 1 more Smart Citation
“…2 The same applies to biological materials that are subjected to extreme loads. [3][4][5][6][7][8][9] The dermal armor of fish is a splendid example where the toughness is essential. [10][11][12][13][14][15][16][17] Arapaima gigas are a large Amazonian fish (weighing up to 150 kgf) living primarily in seasonal lakes infested with ferocious piranhas.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the hybrid design approach provides an alternative to the hierarchical design approach in improving mechanical performance. In Figure 2D, the hierarchical structures inspired by baleen were studied by using advanced multimaterial 3D-printed models (Wang et al, 2018). The simulation results show that the incorporation of the stiff "mineral" component (Model IV) leads to the largest increase in rate stiffening and strengthening.…”
Section: Hierarchical and Helical Structuresmentioning
confidence: 99%